Effects of tilapia (Oreochromis niloticus L.) stocking and artificial feeding on water quality and production in rohu–common carp bi-culture ponds - Rahman, Mohammad Mustafizur; Verdegem, Marc; Wahab, Md Abdul (Wiley-Blackwell, 2008)
Previous research showed that stocking1.5 rohu (Labeo rohita) and 0.5 common carp (Cyprinus carpio) m-2 yields the highest production in small holder ponds in Bangladesh.The present studylooked into the e¡ects of additional stocking of Nile tilapia (Oreochromis nilotica) in fed or non-fed ponds on water quality and ¢sh production. A low, additional stocking density of 0.2 Nile tilapia m-2 was tested. All treatments were executed in triplicate in 100m2 ponds and the duration of the experiment was 4.5 months. The results showed that tilapia addition increased nutrient concentrations and reduced total suspended solid concentration and phytoplankton biomass (Po0.05). Tilapia stocking resulted in additional production without a¡ecting the growth and production of rohu and common carp. Supplemental feeding increased the nitrogen and phosphorus concentrations, phytoplankton availability and the growth and production of rohu and common carp (Po0.01).The combination of supplemental feeding and tilapia stocking resulted in a higher net yield than the other treatments (Po0.05). Stocking 1.5 rohu, 0.5 common carp and 0.2 tilapia m-2 in fed-ponds is a good culture combination for polyculture farmers in South Asia.